SOME RESULT OF NON-COPRIME GRAPH OF INTEGERS MODULO n GROUP FOR n A PRIME POWER - Masriani Masriani; Rina Juliana; Abdul Gazir Syarifudin; I Gede Adhitya Wisnu Wardhana; Irwansyah Irwansyah; Ni Wayan Switrayni (Diponegoro University, 2020)
One interesting topic in algebra and graph theory is a graph representation of a group, especially the representation of a group using a non-coprime graph. In this paper, we describe the non-coprime graph of integers modulo group and its subgroups, for is a prime power or is a product of two distinct primes.